Forest carbon storage along the north-south transect of eastern China: Spatial patterns, allocation, and influencing factors. (February 2016) - Wen, Ding; He, Nianpeng
Highlights: No significant latitudinal pattern for forest C storage (vegetation + soil). The latitudinal patterns of C storage are opposite between vegetation and soil. Latitudinal patterns of C storage become stronger with increasing statistical scale. The ratios of forest C storage (vegetation: soil) decrease with latitude. Climate controlled the patterns of C storage in vegetation, soil, and their ratios. Abstract: Forests play an important role in sequestrating atmospheric CO2 ; therefore, understanding the spatial variations and controlling mechanisms of forest carbon (C) storage is important. In this study, we collected data on forest C storage along a north-south transect of eastern China from literature published between 2004 and 2014. The collected data, which were from over 2000 plots, allowed us to explore the latitudinal patterns in forest C storage. The results showed that vegetation C storage decreased with increasing latitude, while soil C storage increased. This spatial pattern of vegetation C storage was more apparent for mature forests (forest age > 80 years). Furthermore, latitudinal patterns in forest C storage, both in vegetation and in soil, became stronger with increasing statistical scale, increasing from plot scale to latitudinal scale (2–5°). However, total forest C storage (vegetation + soil) had no apparent latitudinal pattern. Interestingly, the allocation ratios of forest C storage between vegetation and soil had a negative logarithmic relationship with latitude. These results suggest that in eastern China, climatic factors control latitudinal patterns in the forest C storage of vegetation and soil, albeit in different ways (positive for vegetation and negative for soil), and also control the allocation ratios of forest C storage between vegetation and soil. Furthermore, the latitudinal patterns of forest C storage were opposite for vegetation and soil, resulting from the different climatic controlling mechanism.